2016
DOI: 10.1038/srep25593
|View full text |Cite
|
Sign up to set email alerts
|

Treponema pallidum Lipoprotein TP0435 Expressed in Borrelia burgdorferi Produces Multiple Surface/Periplasmic Isoforms and mediates Adherence

Abstract: The ability of Treponema pallidum, the syphilis spirochete to colonize various tissues requires the presence of surface-exposed adhesins that have been difficult to identify due to the inability to culture and genetically manipulate T. pallidum. Using a Borrelia burgdorferi-based heterologous system and gain-in-function approach, we show for the first time that a highly immunogenic lipoprotein TP0435 can be differentially processed into multiple isoforms with one variant stochastically displayed on the spiroch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
77
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(83 citation statements)
references
References 54 publications
6
77
0
Order By: Relevance
“…For those antibodies that are potentially opsonic, the extremely low copy numbers of the target proteins likely limits their accessibility, as evidenced by the sizable percentage of treponemes that fail to become surface-labeled or opsonized by high-titer recombinant antisera against TprC/D or BamA 59,65 . Similarly, recent studies suggest that the TP0750–TP0751 protease complex 74,75 and TP0435 78 are expressed at low levels on the surfaces of some treponemes and, consequently, of limited availablity to antibody binding. Two distinct mechanisms for modulating antibody reactivity with Tprs have been proposed.…”
Section: The Face Of Stealth-the Outer Membranementioning
confidence: 92%
See 1 more Smart Citation
“…For those antibodies that are potentially opsonic, the extremely low copy numbers of the target proteins likely limits their accessibility, as evidenced by the sizable percentage of treponemes that fail to become surface-labeled or opsonized by high-titer recombinant antisera against TprC/D or BamA 59,65 . Similarly, recent studies suggest that the TP0750–TP0751 protease complex 74,75 and TP0435 78 are expressed at low levels on the surfaces of some treponemes and, consequently, of limited availablity to antibody binding. Two distinct mechanisms for modulating antibody reactivity with Tprs have been proposed.…”
Section: The Face Of Stealth-the Outer Membranementioning
confidence: 92%
“…The lipoprotein TP0136 is a fibronectin-binding adhesin with sequence heterogeneity among T. pallidum strains (Table 1) 76,77 . Most recently, elegant gain of function experiements using B. burgdorferi as a surrogate genetic host have shown that the lipoprotein TP0435 (Tpp17) functions as a cytadhesin 78 .…”
Section: The Face Of Stealth-the Outer Membranementioning
confidence: 99%
“…The X-ray structure of TP0751, demonstrating an unusual lipocalin fold, should inform efforts to clarify its multi-functionality 79 . Additionally, the lipoprotein Tpp17 (also known as TP0435) has been shown to be at least partially surface-exposed and can function as a cytadhesin 82 . The structurally characterized lipoprotein TP0453 attaches to the inner leaflet of the outer membrane via its N-terminal lipids and two amphipathic helices within its protein moiety 83 .…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
“…The picture emerging from our evolving concepts of the spirochete’s molecular architecture is multi-factorial and likely involves copious production of antibodies against subsurface lipoprotein ‘decoys’ 57,110 ; poor target availability owing to low copy numbers of outer membrane proteins and surface-exposed lipoproteins 67,77,82,84,93 ; in the case of bipartite outer membrane proteins, limited production of antibodies against surface-exposed epitopes along with skewed production of antibodies against periplasmic domain 84,93 ; organism-to-organism variation in the levels of expression of outer membrane proteins and outer surface lipoproteins through a variety of mechanisms, including phase variation 82,92,115,116 ; and, in the case of TprK, antigenic variation as a result of intra-genomic recombination 89,92,117 . Additionally, the ability of motile spirochetes to ‘outrun’ infiltrating phagocytes and reach sequestered locations, including the epidermis, could be an under-appreciated aspect of immune evasion 10,102 .…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation